2009
DOI: 10.5194/acp-9-7519-2009
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of influence of aerosol hygroscopic growth on scattering coefficient over rural area near Beijing mega-city

Abstract: Abstract. We investigated aerosol hygroscopic growth property and its influence on scattering coefficient using M9003 nephelometers in coupling with humidity controlled inlet system at a rural site near Beijing mega-city from 24 April to 15 May 2006. Inlet relative humidity was controlled in an increasing range of 40%-90% while aerosol hygroscopic growth factor of scattering coefficient, f (RH=80%) as ratio of scattering coefficient at RH=80% to "dry" scattering coefficient (RH<40%) varied in a range of 1.07-2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 65 publications
4
106
0
2
Order By: Relevance
“…On the other hand, hygroscopic growth decreases aerosol extinction by lowering the refractive index, since the water that is taken up has a smaller refractive index compared to other aerosol components. The positive effect of the aerosol size on aerosol extinction coefficients outweighs the negative effect of the refractive index, leading to an increase in aerosol extinction and a significant degradation in visibility, as has been observed in some field campaigns (Yan et al, 2008a;Pan et al, 2009). Measurements of ambient aerosol hygroscopic properties were conducted in the NCP using a Hygroscopicity Tandem Differential Mobility Analyser (H-TDMA) (Swietlicki et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, hygroscopic growth decreases aerosol extinction by lowering the refractive index, since the water that is taken up has a smaller refractive index compared to other aerosol components. The positive effect of the aerosol size on aerosol extinction coefficients outweighs the negative effect of the refractive index, leading to an increase in aerosol extinction and a significant degradation in visibility, as has been observed in some field campaigns (Yan et al, 2008a;Pan et al, 2009). Measurements of ambient aerosol hygroscopic properties were conducted in the NCP using a Hygroscopicity Tandem Differential Mobility Analyser (H-TDMA) (Swietlicki et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…The total mass concentration of BC is obtained from measurements during the HaChi campaigns in spring and summer 2009 at Wuqing. Based on the reported BC-density range of 1.00∼2.00 g cm −3 (Ouimette and Flagan, 1982;Sloane et al, 1983Sloane et al, , 1984Seinfeld and Pandis, 1998), an average value of 1.5 g cm −3 ) is adopted. The volume fractions of BC and the corresponding refractive indices for dry particles can be calculated using Eqs.…”
Section: Size-resolved Refractive Indices (M(d P Rh))mentioning
confidence: 99%
“…Croft et al suggested a conversion timescale of 4.9 days for altering hydrophobic BC to hydrophilic/mixed BC through physical and oxidation processes (Croft et al, 2005). Here we filtered the data according to the criterion of RH (<40 %) conditions at which aerosol hygroscopicity was very weak even when aerosols were coated by sulfate and nitrate substances (Pan et al, 2009). (3) Baumgardner et al (2002) and Subramanian et al (2010) suggested that ambient air dilution and dispersion should not appreciably alter the ratio of the two species near the source region despite the different thermal velocities and diffusion coefficients of BC and CO. (4) BC and CO from different emissions were well mixed during 48 h of convection, and BC/ CO here referred to a typical value on a regional scale instead of ratios of one specific emission types.…”
Section: Cluster Analysis Of Regional Bc and Co Correlationsmentioning
confidence: 99%
“…The average was lower than that of 418/Mm measured in winter 2004 in Guangzhou (Andreae et al, 2008), and also lower than that of 473/Mm observed at an urban site in Guangzhou during fall 2009 (Tao et al, 2014b), probably due to a large amount of ultrafine/fine particle from vehicles in the urban areas (Wehner et al, 2002;Dai et al, 2015;Zhang et al, 2015). Average b sp values also were revealed to be relatively higher in China's densely populated city clusters, such as 312/Mm over a rural area near the Beijing mega-city in 2006 (Pan et al, 2009), 456/Mm during winter 2010 in Shanghai in the Yangtze River Delta region (Xu et al, 2012), and 293/Mm in 2011 in Chengdu, a mega-city in southwest China (Tao et al, 2014a). The calculated b ext showed a linear relationship with the measured b sp for dry aerosols (Fig.…”
Section: Visibility and Pm 25 Mass Concentrationsmentioning
confidence: 71%